The Role of Youth in the Industrial Revolution Era 4.0 concerning the Negative Scheme of Children with Special Needs - Rosita Dewi, Noer Azizah (Jurusan PGPAUD FIP UNNES, 2020)
Children with special needs are special children, they are different and they have advantages compared to normal children in general. And of course they also have limitations both physically and mentally compared to normal children in general, but a lot of society and lay people who see them with a negative scheme. With the large number of children with special needs who are considered low today, our role as youth in the era of the industrial revolution 4.0 is expected to form openness to the mindset of humans as social creatures in the environment and also regarding views of children with special needs. Actually, children with special needs also have human rights as human beings that must be guaranteed, protected, and fulfilled by parents, families, communities, governments, and countries. Our duty as youth is very important to give understanding to the community about children with special needs. The method used in this article is literature study. This study aims to make us think more openly with the presence of children with special needs, especially in the era of the industrial revolution 4.0.